Clinical Implications of the Coexistence of Anemia and Diabetes Mellitus in the Elderly Population - S. S. Michalak; E. Wolny-Rokicka; E. Nowakowska; M. Michalak; L. Gil (Journal of Diabetes Research)
Diabetes mellitus (DM) and also anemia are common in the elderly and have a negative impact on the clinical outcomes of patients. The coexistence of anemia and DM seems to be insufficiently recognized; therefore, the aim of our study is to analyze the incidence and clinical consequences of this coexistence, including mortality, in the population of people aged ≥60. A retrospective study was conducted on 981 primary care clinic patients aged ≥60 during 2013-2014. The prevalence of coexistence of DM and anemia (defined in accordance with WHO) and data on the incidence of comorbidities, hospitalization, medical procedures, and all-cause mortality were analyzed. In the study population, 25% had DM, while 5.4% had both DM and anemia. Peripheral artery disease (PAD) was found in 48 patients (4.89%) of the entire study population, more often in men (p<0.001). Diabetic patients with anemia compared to nonanemic diabetics had more comorbidities (median 4 (4, 5) vs. 3 (2–4); p<0.001)—PAD more often (p=0.004), more hospitalization (median 2 (0–11) vs. 0 (0–11); p<0.001), and more frequent medical procedures (e.g., percutaneous coronary intervention (p<0.001), coronary artery bypass surgery (p=0.027), arteriography (p<0.001), and bypass surgery or endovascular treatments of lower limb ischemia (p<0.001)). The cumulative survival of patients with both DM and anemia vs. nonanemic diabetics at 36 months was 86.4% vs. 99.3% (p<0.001). A multivariate logistic regression model showed anemia to be a significant risk factor for death in diabetic patients (p=0.013). Patients with both DM and anemia have more comorbidities than nonanemic diabetic patients; they are more often hospitalized, require medical procedures more frequently, and are at a higher risk of death. Effective treatment of anemia in patients with DM is advisable and may well improve the prognosis of patients.